Non-state actor interference in diplomacy: the American Colonization Society and the U.S. - Liberia relationship (1862-1878) - Barbara FRANCHI (E-REA)
As the founder of Liberia, the American Colonization Society (ACS) was instrumental in modeling the institutions of this country. Therefore, the role of this private organization is of paramount importance when studying the building of the U.S.-Liberia relationship. Before the U.S. recognition of Liberia in 1862, the conduct of U.S. policy towards this country was largely delegated to the ACS. The article raises the question of the evolution of the historical ACS-Liberia relationship after 1862 and sheds light on the influence of the ACS on the diplomatic relations that developed between the two countries until the mission of the first black American appointed U.S. Minister Resident and Consul General to Liberia. Despite a majority of historians having explained that the ACS lost strength in the aftermath of the U.S. Civil War, it shows that this organization maintained an active relationship with Liberia and that it remained influential in the decade that followed the abolition of slavery. The U.S.-Liberia relationship was thus marked by an institutional in-betweenness, the ACS and the U.S. diplomats representing two actors interacting with Liberia. Through an analysis of the diplomats’ official dispatches and the correspondence of the ACS, it further argues that the organization directly interfered in the diplomatic relationship.